Magnitude of common mental disorders and factors associated among people living in Addis Ababa Ethiopia 2018: community based cross-sectional study - Habtamu, Yodit; Admasu, Kalkidan; Tullu, Mikiyas; Kebede, Alem (BMC psychiatry, 2022)
Common mental disorders are a group of distress states manifesting with anxiety, depressive and unexplained somatic symptoms, affecting individuals in different age groups, causes suffering to the individuals, families and community. This study assessed the magnitude of Common mental disorder and associated factors among people living in Addis Ababa, Ethiopia. Community based cross sectional study design was conducted from November 1 to 30, 2018 among people living in Addis Ababa, Ethiopia. Multistage sampling technique was used to get a total of 755 samples. Common Mental Disorder was assessed through interview using Self-Reported questionnaire (SRQ-20). The collected data were coded, entered into EPI-Info 7 and analysed by using SPPS version 20. Descriptive, analytical statistical procedure; bivariate and multivariate binary logistic regressions with odds ratios and 95% confidence interval was employed. The statistical significance was accepted at p value < 0.05. In this study a total of 723 study subjects were participated, with response rate of 95.7%.The prevalence of common mental disorders was 24.7% with [95%CI; 21.6 - 27.7]. Females (AOR=2.1; 95% CI; 1.39- 3.23), Divorced/widowed (AOR=2.55; 95% CI; 1.16- 5.59), daily labourers (AOR=2.52; 95% CI; 1.3- 4.88, chronic medical illness (AOR=4.5; 95% CI; 2.46- 8.24). are independent predictors of CMD and educational status (primary, secondary and diploma) was positively associated with CMD. in this study. Regarding education (primary, secondary and diploma) (AOR=0.34; 95% CI; 0.17-0.66) and (AOR=0.35; 95% CI; 0.19-0.67) has positively associated with common mental disorders. The prevalence of common mental disorders was found high. Female sex, marital status like Divorced/Widowed, daily labour workers and chronic medical illness were found to be independent predictors of CMD and educational status (primary, secondary school and diploma holders) was were found to be protective factors.